COVID‐19 and involuntary detention: An emergency medicine or emergency management responsibility?. (17th January 2022) - Wilson, Joel; Dean, Jessica; Cunningham, Nicola
Abstract: The COVID‐19 pandemic has thrown up innumerable challenges throughout the world, especially evident in the healthcare system. In emergency medicine, there is a new urgency around the clinical and ethical dilemmas clinicians face as they make decisions that impact upon the lives of their patients. Emergency clinicians are accustomed to upholding duty of care and acting in the best interests of patients. Clinical judgements are made every day about a patient's capacity to make their own decisions and act with free will. It is foreseeable that a duty of care owed to a patient may be in conflict with the responsibility to the health and safety of a community. What is particularly fraught for clinicians is the lack of clarity around this potential duty of care to the community, and navigating the potential conflict with duty of care to the patient. How much danger does the community need to be in, and how definable, imminent and specific does that risk need to be? An attempt to protect the community may well constitute either a breach of confidentiality or a breach of duty of care. This paper will explore the complex issues of respect for autonomy and the principle of non‐maleficence, in the setting of COVID‐19 and public health orders and illustrate the uncomfortable uncertainty that exists surrounding care of some of the most vulnerable patients in the community when their actions are contrary to public health recommendations.